Layer-by-layer assembly of light-responsive polymeric multilayer systems - Borges, J. (2014)
Layer-by-Layer (LbL) assembly is a simple and highly versatile method tomodify surfaces and fabricate robust and highly-ordered nanostructured coatingsover almost any type of substrate. Such versatility enables the incorporationof a plethora of building blocks, including materials exhibiting switchableproperties, in a single device through a multitude of complementary intermolecularinteractions. Switchable materials may undergo reversible physicochemicalchanges in response to a variety of external triggers. Althoughmost of the works in the literature have been focusing on stimuli-responsivematerials that are sensitive to common triggers such as pH, ionic strength, ortemperature, much less has been discussed on LbL systems which are sensitiveto non-invasive and easily controlled light stimulus, despite its uniquepotential. This review provides a deep overview of the recent progressesachieved in the design and fabrication of light-responsive LbL polymericmultilayer systems, their potential future challenges and opportunities, andpossible applications. Many examples are given on light-responsive polymericmultilayer assemblies built from metal nanoparticles, functional dyes, and metal oxides. Such stimuli-responsive functional materials, and combinationsamong them, may lead to novel and highly promising nanostructured smartfunctional systems well-suited for a wide range of research fields, includingbiomedicine and biotechnology.